Basic Principles of Interdisciplinary Risk Management (Economic and Political Thought, 2011)
The article presents basic principles of risk management, i.e. risk identificationand analysis, risk assessment and specification of its variants, andmethods of risk limitation and elimination. It highlights an issue of increasinginformation resources of various fields and branches of economy. It extensivelydiscusses an issue of how to effectively counteract diversified risk. Thetheoretical presentation of Risk Management was illustrated by examplesoriginating from international trade.